Past-Oral Care – Christian Hope in Pastoral Care and Counseling for People With Severe Dementia in Finland - Pirhonen, Jari (Journal of pastoral theology, 2023)
This article explores the possibility of time-bound hope for people with severe dementia residing in nursing homes in Finland. We begin with a short introduction to dementia and move on to unraveling the concept of hope and its connection with temporality. Then, by analyzing Lutheran Christian chaplains’ interviews, we present how the temporal dimensions of past, present, and future may be seen and utilized in pastoral care and counseling of people who have lost their own sense of temporality. While doing this, we introduce the concept of past-oral care to capture the basic nature of the chaplains’ work in nursing homes. In the end, we discuss the nature of Christian faith in the light of this new knowledge.